Warrior of the Altaii - Jordan, Robert, 1948-2007 (Tor fantasy, 2019)
The waterholes of the Plain are drying up, and Wulfgar, leader of the Altaii people faces many other challenges. This is Robert Jordan's never-before-published first novel, which he wrote before his well-known Wheel of Time series.